A Distinctive Adnexal (Usually Paratubal) Neoplasm Often Associated With Peutz-Jeghers Syndrome and Characterized by STK11 Alterations (STK11 Adnexal Tumor): A Report of 22 Cases. (August 2021) - Bennett, Jennifer A.; Young, Robert H.; Howitt, Brooke E.; Croce, Sabrina; Wanjari, Pankhuri; Zhen, Chaojie; Da Cruz Paula, Arnaud; Meserve, Emily; Schoolmeester, J. Kenneth; Westbom-Fremer, Sofia; Benzi, Eduardo; Patil, Ninad M.; et al.
Abstract : We describe 22 examples of a novel, usually paratubal, adnexal tumor associated with Peutz-Jeghers syndrome in nearly 50% of cases that harbored STK11 alterations in all tested (n=21). The patients ranged from 17 to 66 years (median=39 y) and the tumors from 4.5 to 25.5 cm (median=11 cm). Most (n=18) were paratubal, with metastases noted in 11/22 (50%) and recurrences in 12/15 (80%). Morphologically, they were characterized by interanastomosing cords and trabeculae of predominantly epithelioid cells, set in a variably prominent myxoid to focally edematous stroma, that often merged to form tubular, cystic, cribriform, and microacinar formations, reminiscent of salivary gland-type tumors. The tumor cells were uniformly atypical, often with prominent nucleoli and a variable mitotic index (median=9/10 HPFs). The tumors were usually positive to a variable extent for epithelial (CAM5.2, AE1/AE3, cytokeratin 7), sex cord (calretinin, inhibin, WT1), and mesothelial (calretinin, D2-40) markers, as well as hormone receptors. PAX8, SF1, and GATA-3 were rarely positive, while claudin-4, FOXL2, and TTF-1 were consistently negative. All sequenced tumors (n=21) harbored alterations in STK11, often with a loss of heterozygosity event. There were no other recurrently mutated genes. Recurrent copy number alterations included loss of 1p and 11q, and gain of 1q, 15q, and 15p. Despite an extensive morphologic, immunohistochemical, and molecular evaluation, we are unable to determine with certainty the histogenesis of this unique tumor. Wolffian, sex cord stromal, epithelial, and mesothelial origins were considered. We propose the term STK11 adnexal tumor to describe this novel entity and emphasize the importance of genetic counseling in these patients as a significant number of neoplasms occur in association with Peutz-Jeghers syndrome. Abstract : Supplemental Digital Content is available in the text.